1999
DOI: 10.1097/00006454-199911000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella pneumoniae with extended spectrum beta-lactamase activity associated with a necrotizing enterocolitis outbreak

Abstract: The isolation of a single clone of K. pneumoniae with extended spectrum of beta-lactamase activity during an NEC outbreak highlights the need for strict infection control. This organism caused significant morbidity and was difficult to treat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…Many studies on outbreaks of NEC reported either very low rates of NEC11–13, 17, 19, 22, 31 or did not report a background rate,10, 14, 15, 18, 29, 32 leading the reader to assume that perhaps that particular site typically sees a minimal number of NEC cases within their institution. Our NICUs have a relatively endemic rate of NEC.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies on outbreaks of NEC reported either very low rates of NEC11–13, 17, 19, 22, 31 or did not report a background rate,10, 14, 15, 18, 29, 32 leading the reader to assume that perhaps that particular site typically sees a minimal number of NEC cases within their institution. Our NICUs have a relatively endemic rate of NEC.…”
Section: Discussionmentioning
confidence: 99%
“…Klebsiella species is the most frequent aerobic species implicated in NEC, but most microbiologic analyses of NEC cases involving Klebsiella did not include anaerobic microflora cultures (17,18). Westra-Meijer et al (19), comparing aerobic and anaerobic fecal flora in healthy preterm infants and infants with NEC, observed a higher colonization with Klebsiella species in infants with NEC but no difference in clostridia populations.…”
Section: Discussionmentioning
confidence: 99%
“…55,56 Klebsiella pneumoniae: Extended-spectrum b-lactamaseproducing strains of K. pneumoniae have been reported to cause hospital outbreaks of sepsis associated with a high incidence of NEC. 57,58 Acinetobacter: There has been a cluster of sepsis cases related to Acinetobacter. In five patients, the condition was also associated with NEC.…”
Section: Viral Agentsmentioning
confidence: 99%